Determination of G2 Erosion Model Parameters With Photogrammetry and Remote Sensing Data - Edyta Kruk; Przemyslaw Klapa; Marek Ryczek; Tomasz Kowalik (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Photogrammetric and remote sensing studies have a wide range of applications. They are popular data sources for various purposes, including spatial analysis, site and object surveys, and environmental studies. Research aimed at developing an optimal and reliable erosion model requires a specialized and comprehensive approach due to the numerous natural and anthropogenic factors that must be considered. Physical and chemical characteristics of soils change according to land-use practices, terrain topography, and prevailing meteorological conditions. Such diverse issues require detailed and specific investigations. Data for these studies can be obtained through spatial analyses based on remote sensing and photogrammetric data as well as thematic cartographic studies. We present a method for acquiring and processing various types of geospatial data using geographic information system (GIS) tools to generate the individual parameters required in the G2 erosion model. This article was conducted in an area covering 36.3 km2, corresponding to the Odra River watershed in the Silesian Voivodeship, Poland. This article employed publicly available high-resolution thematic layers, such as high-resolution layers from the Copernicus Land Monitoring Service and Sentinel-2. Methods such as remote sensing, GIS analysis, and normalization of available parameters were used to determine various parameters of the G2 erosion model. This effort yielded a high-resolution erosion map, facilitating the accurate determination of the model parameters at any given location on the site.